Safety and efficacy of a super critical carbon dioxide extract of Humulus lupulus L. flos when used as a feed flavouring for all animal species. (30th October 2018) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of a super critical carbon dioxide extract of Humulus lupulus L. flos (hop strobiles) when used as a sensory feed additive for all animal species. The additive is specified to containing 40% beta acids and less than 0.2% alpha acids. Known substances of concern ■■■■■ were not detected. It is intended for use as a sensory additive for all animal species at a maximum application rate of 50 mg additive/kg complete feed. Tolerance studies were provided with weaned piglets, chickens for fattening, dairy cows and fish in support of the application for all animal species. However, the FEEDAP Panel could only conclude that the additive is safe for weaned piglets, pigs for fattening and minor growing porcine species at the maximum proposed application rate. No concerns for consumer safety were identified for the use of the additive at the proposed use level in animal nutrition. In the presence of water, the additive is corrosive to skin and eyes. The additive is a potential respiratory and skin sensitiser. Use of the additive in animal production is not expected to pose a risk for the terrestrial or fresh water environment. Since harvested hop and its extracts are recognised to flavour food and its function in feed would be essentially the same as that in food, no further demonstration of efficacy is considered necessary.